The roles of circulating neonatal nav1.5 (NNAV1.5) and its antibodies in cancer progression of 4T1 orthotopic mice model and breast cancer patients - Rajaratinam, Harishini A/P (2023)
The study has aimed to investigate the roles of circulating neonatal Nav1.5 (nNav1.5) and natural antibodies produced against nNav1.5 (anti-nNav1.5-Ab) in the whole blood and serum of 4T1 orthotopic mice model and breast cancer patients. The preclinical research involved three mice groups: control (n=20), 4T1 orthotopic breast cancer model (n=17), and positive control (n=3). Blood samples, target organs and 4T1 tumours were collected. Real-time polymerase chain reaction (qPCR) was conducted to detect the expression of nNav1.5 antigen in the whole blood and an in-house indirect enzyme-linked immunosorbent assay (ELISA) was used to detect the expression of anti-nNav1.5-Ab in the serum. Additionally, lung metastasis clonogenic assay, histology and cytokine analysis were conducted. The clinical study involved 128 participants: healthy participants (n=64) and breast cancer patients (n=64). The sociodemographic details of the participants were analysed. The breast cancer patients were divided based on their treatment status and stages. A total of 6 ml of blood was withdrawn, and similarly, qPCR and ELISA were conducted to detect the circulating nNav1.5 and anti-nNav1.5-Ab, respectively. The cytokine analysis was also conducted in the clinical study. The preclinical study revealed the occurrence of metastasis (via clonogenic assay and histology) and circulating nNav1.5 antigen in 4T1 orthotopic mice. The 4T1 orthotopic mice showed significantly higher absorbance of antinNav1.5- Ab than the control group (P<.001). There was a significant negative correlation between the expression of the nNav1.5 antigen and the absorbance of antinNav1.5- Ab (P<.05, r=-0.549). In the cytokine analyses, there were significant positive correlations between anti-nNav1.5-Ab, IL-6 (P<.05, r=0.643) and VEGF (P<.01, r=0.735). Sociodemographic analysis revealed a significant age difference between healthy participants and breast cancer patients (P<.001). The clinical study showed restricted expression of circulating nNav1.5 antigen, only in five pretreatment patients. The expression of anti-nNav1.5-Ab was detected in both healthy and breast cancer patients, but the absorbance of anti-nNav1.5-Ab was significantly higher in breast cancer patients (P<.001). The pretreatment group portrayed significantly the highest expression of anti-nNav1.5-Ab as compared to the control and ongoing treatment group (P<.001). There was a significant positive correlation between antinNav1.5- Ab and IL-6 (P<.05, r=0.726) in the pretreatment group, followed by a significant negative correlation between anti-nNav1.5-Ab and VEGF (P<.01, r=- 0.842) in the ongoing treatment group. Advanced stage patients exhibited significantly higher expression of anti-nNav1.5-Ab compared to early-invasive patients (P<.05). The presence of anti-nNav1.5-Ab highlights the immunogenicity of nNav1.5. AntinNav1.5- Ab could serve as an immunosurveillance marker for breast cancer metastasis.